Peran Bank Sampah dalam Mewujudkan Masyarakat Peduli Sampah - Afifah, Hasna; Budiaman; Purwandari, Dian Alfia (IAI Nasional Laa Roiba Bogor, 2024)
This research was conducted at the Amanah Bersama Waste Bank located in East Cilandak with the aim of finding out the role of waste banks in creating a waste-caring society. The method used in this research is qualitative. The data collection techniques used are observation, interviews and documentation. Interviews were conducted with the Chairman of Amanah Bersama Waste Bank and the community as customers. The data analysis techniques used are data reduction, data presentation and conclusion drawing. The results of the research that has been carried out are: (1) Amanah Bersama Waste Bank has a waste management program and community education program aimed at creating a clean and healthy environment, as well as creating a society that cares about waste, (2) Public awareness and the presence of a waste bank as an institution community waste management is a factor that influences the community in managing waste, (3) Community participation in the waste bank program based on the Arnstein Ladder is included in the form of consultation participation, namely the community already knows the benefits of the program, knows the program information, voluntarily participates in the program, the community can provide opinions, criticism and suggestions as well as considerations from the waste bank, (4) Community and government participation is very important and necessary for the success of the waste bank in carrying out its role in managing community waste.